The role and effectiveness of integrated development planning (IDP) on service delivery in Vhembe District Municipality - Tshikovha, Nenweli Cedric (University of Limpopo (Turfloop Campus), 2006)
In this study the researcher wanted to disclose the problems undermining the role and effectiveness of IDP for service delivery in the Vhembe District Municipality. The study succeeded in investigating the role and effectiveness of IDP on service delivery in Vhembe District Municipality. The research questions: “is there a role and effectiveness of the Integrated Development Planning in Vhembe District Municipality on service delivery?” and “is there a significant improvement of municipal services since the introduction of the IDP process in the year 2000?” and finally, “Is the IDP of Vhembe District Municipality Linked to the Budget?” were interrogated. The specific objectives of the study which include “investigating how the IDP impacts on service delivery” were outlined. The study also endeavoured to satisfy the second objective by suggesting possible solutions as to how the IDPs could be strengthened to address service delivery constraints and challenges. The research also looked at the historical background of Integrated Development Planning. In doing so, the research looked at the development planning evolution in South Africa. Policy and Legislative Framework governing the formulation and implementation of the IDP in South Africa were also considered. The study strove to outline the problems and other dynamics associated with linkage of the IDP to the budgeting process. Public participation and the role of provincial and national government departments in the IDP were also looked into. Three methods of data collection were identified for use in this study, namely: unstructured interviews, participant observation and documentation. The population for the study comprised the stakeholders for IDP. This was divided into government officials and members of community. Purposive sampling was conducted to each group of the population. The researcher presented data in an explanatory way. The main problem identified on the role and effectiveness of the IDP is its lack of alignment with the budget of the municipality. Recommendations were made at the end of the study.
Thesis (M.Dev.) --University of Limpopo
Keywords: Integrated development planning; Municipality service delivery; 338.968; Economic development -- South Africa